Stan dzisiejszy i historia polonistyki na Uniwersytecie Wileńskim - Dalecka, Teresa (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The Department of Polish Studies at the University of Vilnius was established in 1993. This was the result of the processes, negotiations and agreements between Lithuania and Poland that were taking place in 1990 and later (at the same time Lithuanian Studies were introduced at the University of Warsaw). The aim of these activities was to create an educational and research center which would welcome representatives of all nationalities living in Lithuania. The main task of the department was to create and educate specialists in Polish language and culture for educational and cultural institutions, Polish-Lithuanian companies and organizations, as well as to conduct all research concerning the Polish-Lithuanian literary relations and Polish language in Lithuania. After having completed the program, graduates receive the academic title of Bachelor of Arts in Polish Philology. Main areas of employment are schools, translation agencies, educational institutions, various organizations implementing activities in the area of international cooperation.